A new diverse charophyte flora and biozonation of the Eocene bauxite cover-sequence at Gánt (Vértes Hills, Hungary). (3rd April 2021) - Trabelsi, Khaled; Sames, Benjamin; Wagreich, Michael; Kázmér, Miklós; Mindszenty, Andrea; Martín-Closas, Carles
Abstract : A diverse Eocene charophyte flora from a section at Gánt (Vértes Hills), Transdanubian Central Range, north-western Hungary, provides significant new information building on previous studies based only on sub-surface data published from the mid-twentieth century. This newly acquired material facilitates the taxonomic revision and emendation of the species Raskyella peckii and thereby defines a new anagenetic lineage based on three successive varieties that were formerly considered as separate species or subspecies: Raskyella peckii var. peckii (early Lutetian–early Bartonian), Raskyella peckii var. caliciformis (early Bartonian), and Raskyella peckii var. vadaszii (late Bartonian). Based on this lineage, we propose a new local charophyte biozonation that consists of a ' Raskyella peckii Superzone' (Lutetian–Bartonian), sub-divided into three successive charophyte partial range zones: the ' Raskyella peckii peckii Zone' (Lutetian–lower-most Bartonian) characterized by an assemblage of R . peckii peckii, Gyrogona caelata forma caelata, G . caelata forma monolifera and Nitellopsis ( Tectochara ) aff. palaeohungarica, the ' Raskyella peckii caliciformis Zone' (lower Bartonian) characterized by the assemblage of R . peckii var. caliciformis, G . caelata forma caelata, G . caelata forma monolifera, G . caelata forma baccata, Nitellopsis ( Tectochara ) aff. palaeohungarica and Chara media, and the ' Raskyella peckii vadaszii Zone' (upper Bartonian) characterized by R . peckii var. vadaszii, G . caelata forma bicincta, G . caelata forma baccata, G . caelata forma fasciata, G . tuberosa, Psilochara polita, Psilochara sp., Chara media and Chara subcylindrica . Future research may show the new local biozonation as applicable to the whole of Europe and complementary to the current European charophyte biozonation. Our results show that the sequences from Gánt, which were previously regarded as upper mid-Eocene (upper Lutetian–lower Bartonian) in age, appear to represent a longer chronostratigraphic interval: lower Lutetian to upper Bartonian. Our chronostratigraphic results imply a longer and more stepwise Eocene major transgression in the Transdanubian Central Range than previously thought.